TGF-β family co-receptor function and signaling. (27th December 2017) - Nickel, Joachim; ten Dijke, Peter; Mueller, Thomas D
Abstract: Transforming growth factor-β (TGF-β) family members, which include TGF-βs, activins and bone morphogenetic proteins, are pleiotropic cytokines that elicit cell type-specific effects in a highly context-dependent manner in many different tissues. These secreted protein ligands signal via single-transmembrane Type I and Type II serine/threonine kinase receptors and intracellular SMAD transcription factors. Deregulation in signaling has been implicated in a broad array of diseases, and implicate the need for intricate fine tuning in cellular signaling responses. One important emerging mechanism by which TGF-β family receptor signaling intensity, duration, specificity and diversity are regulated and/or mediated is through cell surface co-receptors. Here, we provide an overview of the co-receptors that have been identified for TGF-β family members. While some appear to be specific to TGF-β family members, others are shared with other pathways and provide possible ways for signal integration. This review focuses on novel functions of TGF-β family co-receptors, which continue to be discovered.